Chimney‐Like Intense Pelagic Upwelling in the Center of Basin‐Scale Cyclonic Gyres in Large Lake Geneva - Hamze‐Ziabari, S. M.; Lemmin, U.; Foroughan, M.; Reiss, R. S.; Barry, D. A. (Journal of geophysical research. Oceans, 2023)
Basin‐scale quasi‐geostrophic gyres are common features of large lakes subject to Coriolis force. Cyclonic gyres are often characterized by dome‐shaped thermoclines that form due to pelagic upwelling that takes place in their center. At present, the dynamics of pelagic upwelling within the surface mixed layer (SML) of large lakes are poorly documented. A unique combination of high‐resolution 3D numerical modeling, satellite imagery and field observations allowed confirming, for the first time in a lake, the existence of intense pelagic upwelling in the center of cyclonic gyres under strong shallow (summer) and weak deep (winter) stratified conditions/thermocline. Field observations in Lake Geneva revealed that surprisingly intense upwelling from the thermocline to the SML and even to the lake surface occurred as chimney‐like structures of cold water within the SML, as confirmed by Advanced Very High‐Resolution Radiometer data. Results of a calibrated 3D numerical model suggest that the classical Ekman pumping mechanism cannot explain such pelagic upwelling. Analysis of the contribution of various terms in the vertically averaged momentum equation showed that the nonlinear (advective) term dominates, resulting in heterogeneous divergent flows within cyclonic gyres. The combination of nonlinear heterogeneous divergent flow and 3D ageostrophic strain caused by gyre distortion is responsible for the chimney‐like upwelling in the SML. The potential impact of such pelagic upwelling on long‐term observations at a measurement station in the center of Lake Geneva suggests that caution should be exercised when relying on limited (in space and/or time) profile measurements for monitoring and quantifying processes in large lakes. Plain Language Summary Understanding the dynamics of Pelagic Upwelling (PU) is important because it can rapidly transport nutrients upwards from the thermocline into the phototrophic zone and thus can affect the biogeochemical balance of the lake. In large lakes subject to Coriolis force, pelagic upwelling in the center of cyclonic gyres has been observed. At present, little is known about PU within lakes because the processes associated with PU cannot be captured by the low‐resolution numerical models typically used to investigate geostrophic processes, and high‐resolution field observations are lacking. Here, high‐resolution field measurements were combined with 3D numerical simulations and satellite imagery to investigate the PU structure in the center of a cyclonic gyre in Lake Geneva under different stratifications. Field observations documented, for the first time in a lake, details of the 3D velocity and temperature fields in cyclonic gyres. They showed that PU forms a chimney‐like structure of cold water in the center of a cyclonic gyre. The chimney originates in the thermocline layer and can reach the lake surface, as confirmed by satellite images. As the thermocline descends during the cooling season, the chimney‐like upwelling can attain a height of 80 m. Key Points Pelagic upwelling in the center of cyclonic gyres studied by 3D numerical modeling is confirmed by field measurements and remote sensing imagery Chimney‐like pelagic upwelling that reached the surface was induced by cyclonic gyres in the surface mixed layer during summer and winter The 3D ageostrophic strain field caused by gyre distortion, not Ekman pumping, produced a dome‐shaped thermocline and upwelling in the pelagic zone